School Partnership Management with Industry and the World of Work to Improve Student Automotive Skills Competency - Rahmiati Ruwaida; Putu Sudira (Jurnal Pendidikan dan Pengajaran, 2024)
Partnerships play an important role in improving the quality of education. However, many vocational schools must be more optimal in developing industrial work practice partnerships. In this case, the role of partnership policy in the scope of vocational education must involve three important components: the school board, the industrial business world, and vocational high schools. This research aims to analyze the influence of school partnership management with industry and the world of work on increasing students' automotive skills competency. This type of research is quasi-experimental, with the research design being Post-test Only Control Group Design. The sample used in this research consisted of 72 class XI vocational school students. The data collection method uses tests. The data collection instrument uses test questions. The data analysis techniques used in this research are the t-test and ANOVA. The research results show an influence between the management of school partnerships with industry and the world of work on increasing students' automotive skills competency. The impact of partnership management in honesty education has implications, including requiring the development of students' competencies not only to acquire knowledge but also to integrate skills and attitudes in the world of work.